A Roundness Calculation Method and Physical Parameter Analysis of A Porous Medium Model - Ning, Yang (International Journal of Computer Science and Information Technology, 2024)
The rounding degree of particles is an important index of particle morphology. It represents the degree of rounding of the original edges and corners of debris particles. To a certain extent, it can reflect the transportation and deposition process of debris particles and the source properties. Therefore, it is of great significance to explore the rounding law of gravel and the influencing factors of rounding degree for the study of geological sedimentary environment, source analysis and mass transfer process. Therefore, this paper proposes a rounding degree calculation algorithm for fractal porous media model particles with rounding characteristics. Through numerical simulation and theoretical analysis, combined with the geometric parameters of particle morphology, the relationship between particle roundness and area and perimeter parameters is discussed in detail. The results show that roundness is an important factor in the geometric parameters of particles. The change of roundness can significantly affect the geometric shape of particles, and then affect the size and area of particles. It is of great significance for understanding and optimizing the flow characteristics of porous media models.